DARI ANGKA KE NORMA: PENALARAN NUMERIK MEMBENTUK PERTIMBANGAN MORAL DAN KEWARGAAN ANAK SD - Hendrizal, Hendrizal; Marjohan , Marjohan; Zuzano, Fazri; Afizah, Afizah; Daswarman, Daswarman (Study program PGSD FKIP Universitas Bung Hatta, 2025)
This study critically explores the urgency of integrating numerical reasoning into the development of moral judgment and civic awareness among elementary school students. Using a qualitative approach through comprehensive literature analysis, the research examines how numeracy skills interact with ethical decision-making processes and the internalization of civic values within the context of civic and citizenship education. The findings reveal that numeracy should not merely be understood as technical arithmetic skills but as a cognitive framework influencing children’s ability to weigh fairness, solidarity, and social responsibility. The integration of numeracy with moral reasoning enables students to evaluate alternatives more systematically, construct arguments supported by data, and reflect on the broader social implications of their decisions. Furthermore, the study highlights that embedding numeracy in civic education fosters critical thinking, data literacy, and reflective attitudes essential for nurturing democratic citizenship. The implications suggest a need for cross-disciplinary collaboration in curriculum design, ensuring that students not only master quantitative logic but also develop moral sensitivity and civic commitment. In this way, elementary education can play a pivotal role in shaping future generations who are numerically literate, ethically grounded, and socially responsible.